"OK KETUK": Improving Students' Understanding of Periodic System of Elements Material Through Learning Media - Supatmi, Sri (LAVOISIER: Chemistry Education Journal, 2024)
This study aims to improve students' understanding of the material on the periodic system of elements through OK KETUK learning media. OK KETUK is a learning medium for the periodic system of elements that combines element cards and the periodic table. This medium is played by shuffling the cards, determining the electron configuration, period, and group of elements on the front of the card, doing problems on the back of the card, and placing the elements on the periodic table. This research is classroom action research conducted in two cycles. Each cycle consists of planning, implementing, observing, and reflecting. The research subjects were students of class X IPA 1 SMA Santo Yakobus Jakarta for the academic year 2019/2020, with 24 students, consisting of 12 male and 12 female students. The instruments used in this study consisted of learning outcomes tests, teacher and student activity observation sheets, interviews, and field notes. The results showed that OK KETUK learning media could improve students' understanding of the material on the periodic system of elements. The average score increased from 64.79 with 37.50% learning completeness in the first cycle to 83.44 with 91.67% learning completeness in the second cycle at KKM 70.00. Based on the results of the study, the use of OK KETUK learning media can improve students' understanding of the material for the periodic system of elements.